Cardiac Arrhythmias in Patients with COVID-19 Infection – A Single Center Study - Salim, Md Abu; Mahmood, Manzoor; Adhikary, Dipal K; Banerjee, Sajal K; Hoque, Md Harisul; Muqueet, MA; I Khaled, Md Fakhrul; Rahman, Walidur; Singha, Chayan K; Saha, Sujoy K; Fatema, Nilufar; Hasan, Tarek; et al. (University Heart Journal, 2022)
Background: Corona virus disease (COVID-19) has been associated with different cardiac complications including cardiac arrhythmias. Arrhythmias carries a great influence on the outcomes. The pathophysiology of these manifestations remain elusive. This study was aimed to observe the incidence and outcome of cardiac arrhythmia in patients with COVID-19 infection from July 2020 to May 2021. Method: We conducted an observational study of patients ³18 years of age with a clinical diagnosis of COVID -19 infection attending Bangabandhu sheikh Mujib Medical University (BSMMU) with and without cardiac arrhythmias from July 2020 to May 2021. Patients were labeled as having arrhythmia if they had sinus bradycardia (heart rate <40 bpm), A-V block, Atrial fibrillation (AF), atrial flutter (AFL), supraventricular tachycardia (SVT), nonsustained VT, sustained VT, ventricular fibrillation (VF). We excluded those patients presented with Acute Coronary syndrome & cardiogenic shock. Different clinical data including demographics, comorbidities (like Hypertension, Diabetes mellitus, Chronic kidney disease, IHD), baseline electrocardiographic and echocardiographic findings, antiviral therapy, use of any proarrhythmic drugs. Results: Data was collected from 2264 patients from BSMMU with COVID-19 infection. Among them 158 patients (6.97%) had cardiac arrhythmia, 78 (48.91%) had hypertension, 37 (23.41%) ischaemic heart disease, 31 (19.62%) diabetes, 14 (8.88%) had CKD. Out of 158 patients 53.79% had sinus bradycardia (heart rate £40bpm); 16(10.1%) had first degree AV block; 14 (8.86 %) had 2nd or 3rd degree AV block; 27 (17.08%) had AF; 7 (4.40%) had AFL; 6 (3.7%) had SVT; and 3 (1.89%) of had NSVT. Only one of S. bradycardia patient required temporary pacemaker. 80 (93.75%) did not require any specific treatment and 4 ( 6.25%) was ventilated. 14 (8.86%) had advance AV block, 11 (78.57%) was discharged, 1 (7.14%) required permanent pacemaker and 3 (21.42%) needed mechanical ventilation in addition to standard treatment. 40 (25.31%) had AF/AFL/SVT; all of them were treated with different antiarrhythmic drugs. 40.0% needed mechanical ventilation and 60.0% discharged safely. 3 (1.89%) had NSVT or VT, 2 (66.67%) of them needed mechanical ventilation and 1 (33.33%) was discharged safely. 87.32% patient was discharged safely and 16.4% was ventilated. Among 26 ventilated patients 15 (57.69%) was expired. Out of them 11 (68.75% of 16 patient) had atrial tachyarrhythmia, 2 (100% of 2 patient) had ventricular tachyarrhythmia and 2 (16.67% of 12 patient) had bradyarrhythmia. Conclusion: COVID-19 infection made a profound negative effect on the lives of millions of people across the world. More than 3 millions of people already died. Lots of patients of COVID-19 infection developed cardiac arrhythmia and was associated with high morbidity and mortality. Appropriate monitoring by ECG with accurate and early identification of arrhythmia is important for better management and outcome. University Heart Journal 2022; 18(1): 61-64